2018
DOI: 10.1021/acs.orglett.8b03586
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Benzannulated [6,6]-Spiroketals by a One-Pot Carbonylative Sonogashira Coupling/Double Annulation Reaction

Abstract: A one-pot Pd-catalyzed carbonylative Sonogashira coupling in tandem with double annulation reaction to synthesize benzannulated [6,6]-spiroketals from o-iodophenols and terminal alkynols or alkynyl phenols was achieved. The protocol provides straightforward and facile access to benzannulated [6,6]-spiroketals in moderate to good yields and excellent diastereoselectivities under balloon pressure of CO at room temperature. Letter pubs.acs.org/OrgLett

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Furthermore, we carried out a survey of the palladium source to optimize the reaction conditions; however, none of them provided a better yield than Pd­(OAc) 2 (Table , entries 15–17). In recent years, cooperative metal catalytic systems produced numerous applications in oxidative addition and reductive elimination reactions. , The strategy of combining palladium with other metals, such as Pd/Rh, , Pd/Au, Pd/Ni, Pd/Cu, , and Pd/Pd, ,, has been extensively studied in depth. A double Pd­(II)-catalyzed system was commonly used in cross-coupling reactions, for example, the Heck reaction, the Suzuki coupling reaction, or C–H functionalization, which can potentially lower the activation barriers of chemical transformations compared to a single Pd­(II)-catalyzed system. , A further investigation revealed that a cocatalyst combining Pd­(OAc) 2 and Pd­(PhCN) 2 Cl 2 was the best choice, affording the desired product 3a in 70% isolated yield (Table , entries 18–20).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we carried out a survey of the palladium source to optimize the reaction conditions; however, none of them provided a better yield than Pd­(OAc) 2 (Table , entries 15–17). In recent years, cooperative metal catalytic systems produced numerous applications in oxidative addition and reductive elimination reactions. , The strategy of combining palladium with other metals, such as Pd/Rh, , Pd/Au, Pd/Ni, Pd/Cu, , and Pd/Pd, ,, has been extensively studied in depth. A double Pd­(II)-catalyzed system was commonly used in cross-coupling reactions, for example, the Heck reaction, the Suzuki coupling reaction, or C–H functionalization, which can potentially lower the activation barriers of chemical transformations compared to a single Pd­(II)-catalyzed system. , A further investigation revealed that a cocatalyst combining Pd­(OAc) 2 and Pd­(PhCN) 2 Cl 2 was the best choice, affording the desired product 3a in 70% isolated yield (Table , entries 18–20).…”
Section: Resultsmentioning
confidence: 99%
“…Benzannuulated‐[6,6]‐spiroketals were synthesized by a one‐pot Pd‐catalyzed carbonylative Sonogashira coupling in tandem with double annulation reaction from o ‐iodophenols and alkynyl phenols (Scheme 21). [ 128 ]…”
Section: Sonogashira‐related Coupling Reactionsmentioning
confidence: 99%
“…The synthesis of pyran-and chroman-2-spiro-4H-chroman-4-ones occurs via onepot palladium(II)-catalyzed carbonylative Sonogashira coupling/double annulation reaction of 2-iodophenols with terminal alkynols or alkynyl phenols carried out in the presence of copper(I) iodide and DBU or triethylamine under balloon pressure CO, followed by the addition of sodium hydride (Scheme 75) (19OL412).…”
Section: Chromones and Chromanonesmentioning
confidence: 99%